Investor Heterogeneity, Investor-Management Disagreement, and Share Repurchases - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2013)
This paper develops and tests a new theoretical explanation for why a firm conducts open-market stock repurchases. Investors may disagree with the manager about the firm’s investment projects. A repurchase causes a change in the investor base as investors who are more likely to disagree with the manager tender their shares. This model leads to the following predictions. First, a firm is more likely to buy back shares when the level of investor-management agreement is low. Second, the level of agreement improves following a repurchase. Our empirical tests provide strong support for these predictions. The results are robust to controls for information asymmetry, diversity of investor opinion, and other factors that may drive a firm’s share repurchase decision. Overall, the evidence is consistent with firms strategically using repurchases to improve alignment between management and shareholders.